Deep-sea carbonate preservation in the western Philippine Sea over the past 1Ma. (30th November 2017) - Sun, Hanjie; Li, Tiegang; Chang, Fengming; Wan, Shiming; Xiong, Zhifang; An, Baizheng; Sun, Rongtao
Abstract: In this paper, we present a continuous record of calcium carbonate (CaCO3 ) content that covers the last 1 Ma from core MD06-3050 (15°57.0943′N, 124°46.7747′E; water depth, 2967 m), which was collected in the western Philippine Sea (WPS). The CaCO3 content in this study core is characterized by maxima during deglaciations and minima during the onsets of glacial periods and generally shows Pacific-style patterns, with relatively high and low values during glacial and interglacial periods, respectively. Proxies of dissolution and primary productivity (PP), the CaCO3 content and the oxygen isotope record from this core are compared throughout the 1 Ma study interval to improve our understanding of the mechanisms that affected carbonate preservation and dissolution at this site. The planktonic foraminifera shell fragmentation ratio (%shell fragment) is used as a dissolution proxy in this study. The %shell fragment data from MD06-3050 provide evidence of preservation maxima during most of the deglaciations, whereas intense dissolution is recorded at the onsets of glacial periods within the past 1 Ma. The variations in %shell fragments are similar to those seen in the CaCO3 content, which demonstrates that the bulk CaCO3 content patterns were controlled by dissolution in deep seawater. The primary productivity from the coccolith record shows limited similarity with the CaCO3 content on glacial-interglacial time scales since 1 Ma, which suggests that PP played a negligible role in the glacial-interglacial CaCO3 cycle. However, a bloom of the coccolithophores Geophyrocapsa caribbeanica that extended from MIS 9 to MIS 12 likely contributed to the increased CaCO3 content observed during the Mid-Brunhes interval (MBE) over the glacial-interglacial fluctuations. Therefore, the CaCO3 content should be used as a dissolution proxy with caution during the MBE in the tropical Pacific, especially for water depths that are shallower than the carbonate lysocline.